2019
DOI: 10.1039/c9ta09429f
|View full text |Cite
|
Sign up to set email alerts
|

Tellurene based chemical sensor

Abstract: Chemiresistive sensor devices using two-dimensional (2D) materials have been extensively studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 38 publications
3
77
0
2
Order By: Relevance
“…However, such methods face critical challenges in terms of scalability, control over thickness, substrate-free growth, and sensitivity to growth conditions which inhibits its application, especially for energy storage where scalable manufacturing is essential 16 . The recently discovered, hydrothermal method 17,18 can overcome these limitations, and was therefore used in this study for synthesis of Te (grey colored powder, inset of figure S1a) (details regarding the growth mechanism and procedures are provided in Methods).…”
Section: Synthesis Of Tellurenementioning
confidence: 99%
See 2 more Smart Citations
“…However, such methods face critical challenges in terms of scalability, control over thickness, substrate-free growth, and sensitivity to growth conditions which inhibits its application, especially for energy storage where scalable manufacturing is essential 16 . The recently discovered, hydrothermal method 17,18 can overcome these limitations, and was therefore used in this study for synthesis of Te (grey colored powder, inset of figure S1a) (details regarding the growth mechanism and procedures are provided in Methods).…”
Section: Synthesis Of Tellurenementioning
confidence: 99%
“…To circumvent this, tellurium-based nanostructures have been synthesized using several methods, which typically lead to the formation of 1-D tellurium structures (such as nanowires or nanotubes) due to the anisotropic structure of bulk tellurium 16 . However, recently a controllable hydrothermal method has been developed that can lead to the formation of 2-D Tellurium or Tellurene (Te) 17,18 . Te has many attractive features when compared to other materials in the 2D family 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To realize the novel applications of Te NMs, a simple and feasible strategy for synthesizing Te NMs with a controllable and uniform topography in a green method is urgently required. 1,17 To date, various morphologies, such as nanowires, 18 nanorods, 19 nanotubes, 20 nanoflakes, 21 and even tellurene, 22 of Te NMs have been investigated, and the corresponding growth mechanisms have also been developed. For example, the solid-solution-solid growth mechanism and the nucleation-dissolution-recrystallization growth mechanism have been proposed for the generation of Te NWs 23 and Te nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, researchers confirmed that the metal-doped TiO2 sensitive materials have been investigated for application in detecting H2, O2, NO2 and NO, showing a broad application prospect [29][30][31]. Studies showed that sputtering 10 nm thick Pd on the surface of TiO2 nanotubes by thermal evaporation can improve the sensitivity of TiO2 nanotube gas sensor and shorten the recovery time [32][33][34][35]. Furthermore, researchers studied the geometric structures and interactions between Pd cluster and TiO2 nanotubes, where the Pd atom number from 1 to 5 were taken into consideration [36][37][38].…”
Section: Introductionmentioning
confidence: 99%